2018
DOI: 10.5194/acp-18-15451-2018
|View full text |Cite
|
Sign up to set email alerts
|

Primary emissions of glyoxal and methylglyoxal from laboratory measurements of open biomass burning

Abstract: Abstract. We report the emissions of glyoxal and methylglyoxal from the open burning of biomass during the NOAA-led 2016 FIREX intensive at the Fire Sciences Laboratory in Missoula, MT. Both compounds were measured using cavity-enhanced spectroscopy, which is both more sensitive and more selective than methods previously used to determine emissions of these two compounds. A total of 75 burns were conducted, using 33 different fuels in 8 different categories, providing a far more comprehensive dataset for emiss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
53
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 80 publications
(165 reference statements)
12
53
2
Order By: Relevance
“…C 4 H 4 O 3 −H + could be 5-hydroxy-2(5H)-furanone (or simply hydroxy furanone), its tautomer malealdehydic acid, or succinic anhydride, whereas C 4 H 8 O 2 −H + is likely a C 4 hydroxy carbonyl (see Sect. 3.1 and) Liu et al, 1999;Bierbach et al, 1994Bierbach et al, , 1995Alvarez et al, 2009;Aschmann et al, 2011Aschmann et al, , 2014Strollo and Ziemann, 2013;Zhao and Wang, 2017). Due to uncertainties in these assignments, calibration factors for these species are calculated using estimated proton transfer rate constants derived from molecular formula relationships (uncertainty to within a factor of 2, Sekimoto et al, 2017).…”
Section: Nmog Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…C 4 H 4 O 3 −H + could be 5-hydroxy-2(5H)-furanone (or simply hydroxy furanone), its tautomer malealdehydic acid, or succinic anhydride, whereas C 4 H 8 O 2 −H + is likely a C 4 hydroxy carbonyl (see Sect. 3.1 and) Liu et al, 1999;Bierbach et al, 1994Bierbach et al, , 1995Alvarez et al, 2009;Aschmann et al, 2011Aschmann et al, , 2014Strollo and Ziemann, 2013;Zhao and Wang, 2017). Due to uncertainties in these assignments, calibration factors for these species are calculated using estimated proton transfer rate constants derived from molecular formula relationships (uncertainty to within a factor of 2, Sekimoto et al, 2017).…”
Section: Nmog Measurementsmentioning
confidence: 99%
“…2), it is likely that these species are formed from the oxidation of furans, oxygenated aromatics, or other fastreacting NMOGs with C ≥ 4. Several studies have investigated the oxidation of furan species and shown that hydroxy furanone + tautomer (C 4 H 4 O 3 ) and methyl hydroxy furanone + tautomer (C 5 H 6 O 3 ) are major products formed from the oxidation of furfural, furan, 2-methylfuran, and 2,5dimethylfuran (e.g., Bierbach et al, 1994Bierbach et al, , 1995Alvarez et al, 2009;Aschmann et al, 2011Aschmann et al, , 2014Strollo and Ziemann, 2013;Zhao and Wang, 2017). Secondary NMOGs measured from the OH chemistry of oxygenated aromatic species are largely carbon-retaining (C ≥ 6), though C 4 H 4 O 4 ring fragments have been measured in low-NO x catechol oxidation (Yee et al, 2013).…”
Section: Box Model Implementation and Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…(CES) Zarzana et al, 2018), and proton-transfer-reaction time-of-flight 278 mass spectrometer (PTR-ToF). Inlet ports of CES and PTR-ToF were placed 5' apart 279…”
mentioning
confidence: 99%
“…Air was sampled directly 324 from stack at a height of 15 m above the fuel bed through a 1 m length of ¼" O.D. Teflon 325 (FEP) tubing as described inZarzana et al (2018). The residence time in the inlet and 326 sample cells was < 1 s. Comparison between the ACES HONO and an open path FTIR 327…”
mentioning
confidence: 99%